Suspended palladium nanometer half-tube material based on metal contact, preparation method and application
The preparation of suspended palladium nano-semi-tube materials through electrospinning and electron beam evaporation technology solves the problems of complex processes and slow response time of existing palladium-based hydrogen sensors, and realizes a low-cost and high-efficiency high-performance hydrogen sensor.
Patent Information
- Application Number
- CN202411521172.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The existing palladium-based hydrogen sensors have high preparation process, complex process and slow response time, making it difficult to meet the needs of low cost, high efficiency and high performance.
Electrospinning, electron beam evaporation and ultraviolet nanoimprinting technology were used to prepare suspended palladium nano-semi-tube materials based on metal contacts. The nanofibers were transferred to the substrate by water vapor transfer method to form a 10nm-level thin film trench structure.
It realizes the preparation of palladium nano-semi-tube materials at low cost and high efficiency, improves the response speed and gas-sensitive performance of hydrogen sensors, and meets the needs of practical applications.
Smart Images

Figure CN119390006A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of gas sensors, and in particular relates to a suspended palladium nano-half-tube material based on metal contact, a preparation method and an application thereof. Background Art
[0002] In recent years, hydrogen (H2) has attracted widespread attention in the energy and environmental fields as an efficient energy storage method with high energy density, cleanness, and easy distribution. H2 gas is also used in various industrial applications, including petroleum and glass refining, semiconductor and pharmaceutical manufacturing, H2 cooling systems, and metallurgical processes. Although H2 gas can be used in many industrial applications and fuel cells, since the explosion limit of colorless and odorless H2 gas at room temperature is very low, only 4%, it needs to be continuously monitored for its leakage. Therefore, hydrogen sensors with high response, high selectivity, low cost, low power consumption, and high reliability are necessary to ensure hydrogen safety, among which cost and power consumption are the most important considerations for sensors to be used in practical applications.
[0003] At present, palladium-based chemiresistor sensors have attracted much attention as a reliable, efficient and scalable hydrogen sensor because of their ability to selectively detect hydrogen at room temperature. When H2 gas molecules come into contact with Pd, H2 splits into hydrogen atoms on the Pd metal surface and enters the Pd lattice to form PdHx. This phenomenon causes the resistance of Pd to change. Since the change is very small, palladium-based sensors usually only show excellent gas-sensing performance when they have nanoscale structures. Sensors are mainly prepared by micro-nano manufacturing processes such as lithography and MEMS. However, these processes are costly, difficult and complex, which limits the development and application of palladium-based sensors. Therefore, there is an urgent need for a low-cost, simple process and high-performance palladium-based sensor preparation method. In addition, material contact (metal / metal, metal / metal oxide) can affect the chemical and electronic properties of the oxide within the first few nanometers, resulting in changes in the chemical reaction performance, conductivity and energy level arrangement characteristics of the material. These effects can change the ability of the oxide to perform its intended function. Therefore, creating conditions for other metals or metal oxides to contact palladium films is expected to improve their gas-sensing properties, thereby better applying them to hydrogen sensors.
[0004] It is proposed to use electrospinning, electron beam evaporation and ultraviolet nanoimprinting technology to prepare a nanograting supported suspended palladium nanotube structure for hydrogen sensor. Compared with other methods (gas phase method, liquid phase method, template method, hydrothermal method), electrospinning (electrospinning, referred to as "electrospinning") is a simple method for preparing one-dimensional nanomaterials. By adjusting the parameters of the electrospinning process, the diameter, length and surface morphology of the nanofibers can be flexibly adjusted. Electrospinning mainly consists of three parts: high voltage power supply, spinneret and receiving device. Charged polymer melt or solution forms Taylor cones under the combined action of the electric field and surface tension in a high-voltage electrostatic field. When the electric field force is large enough to overcome the surface tension, ejection, stretching, splitting, solidification or solvent volatilization occurs to form fibrous substances. Electron beam evaporation is a process that accelerates electrons to bombard the coating material to heat it and evaporate it, forming a film. It can deposit high-purity and high-precision films. UV nanoimprinting technology can achieve rapid replication and transfer of micro-nanoscale graphic structures, with the advantages of high resolution, high yield and low cost, and can easily produce 3D structures and structures with high aspect ratios.
[0005] At present, there is a phase change suppressed Pd nanowire H2 sensor, which specifically uses an atomic layer deposition system to deposit a 20nm Al2O3 capping layer on a Si nanograting; a Cu sacrificial shadow template is formed by two oblique angle depositions by PVD on the Si nanograting substrate covered with Al2O3; then, a forming gas annealing process is performed at 410℃ for 40min under H2+N2 ambient conditions (1:9 ratio). Then, Pd with a chromium (Cr) adhesion layer is vertically deposited on the area where the nanowire array is to be formed by a boost method with a negative photoresist. After removing the PR and SSP by a photolithography process, another lift-off process is used to form electrodes by aluminum DC sputtering. A measurement device is constructed to detect the gas response of different concentrations of H2 in a nitrogen atmosphere. This method achieves high linearity hydrogen sensing by suppressing the Pd phase change through the grooves of the nanograting and the aluminum oxide contact.
[0006] However, the manufacturing steps of this method include photolithography, boost deposition, oblique angle deposition and other processes, which leads to the problems of high cost, complex process and low efficiency. At the same time, according to the gas-sensitive test results, the sensor has a slow response time. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention provides a method for preparing a suspended palladium nano-half-tube material based on metal contact, comprising the following steps:
[0008] S1: mixing polyvinyl alcohol and a solvent in a mass ratio of 1 to 2:10, stirring evenly by magnetic stirring, degassing to obtain a precursor solution, electrospinning the precursor solution, receiving it with a template, and obtaining polyvinyl alcohol nanofibers;
[0009] S2: Vapor-deposit metal palladium on the polyvinyl alcohol nanofibers obtained in S1, and simultaneously vapor-deposit tin oxide on the substrate, and transfer the fibers to the substrate by water vapor dissolution method to obtain a suspended palladium nano-half-tube material.
[0010] Furthermore, the temperature of magnetic stirring in S1 was 65-85°C, the stirring time was 12 h, and the stirring rate was 600 r·min -1 , degassing rate is 3000r·min -1 The degassing time is 3 to 5 minutes.
[0011] Furthermore, the pushing speed during the spinning process in S1 is 0.1-0.2 mm·min -1 , the DC voltage is 16-20 kV, the distance between the needle tip and the receiving template is 15-20 cm, and the spinning time is 5-15 min.
[0012] Furthermore, the temperature of the spinning process in S1 is 40° C. and the humidity is 20-30 RH; the template is a rectangular hollow template, and the size of the hollow is 100 mm*20 mm.
[0013] Furthermore, the metal palladium in S2 is 10 nm and the coating rate is 0.8 nm / min.
[0014] A suspended palladium nanometer half-tube material based on metal contact, wherein the suspended palladium nanometer half-tube material is a half-tube structure.
[0015] The invention discloses an application of a suspended palladium nanometer half-tube material based on metal contact, wherein the suspended palladium nanometer half-tube material is applied in the preparation of a hydrogen sensor.
[0016] Beneficial Effects
[0017] (1) The present invention provides a suspended palladium nanotube material based on metal contact, a preparation method and an application thereof. PVA nanofibers are used as sacrificial templates, and a water vapor transfer method is proposed to achieve low-cost and high-efficiency preparation of 10nm-level thin film groove structures. The structure can be transferred to any substrate and has rich potential applications.
[0018] (2) The present invention provides a suspended palladium nano half-tube material based on metal contact, a preparation method and an application thereof, which utilizes the half-tube and suspension structure to increase the specific surface area of the palladium film, while reducing the inhibition of the base material on the palladium-hydrogen reaction expansion process to increase the response speed.
[0019] (3) The present invention provides a suspended palladium nanotube material based on metal contact, a preparation method and an application thereof. For the first time, metal oxide is used as a base material in contact with a metal semi-tube to affect the chemical and electronic properties in the gas sensing process, thereby causing changes in the chemical reactivity, electrical conductivity and energy level arrangement characteristics of the metal and the metal oxide. These influences can change the gas sensing performance of the sensor. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For ordinary technicians in this field, other relevant drawings can be obtained based on these drawings without creative work.
[0021] In the figure:
[0022] Figure 1 A schematic diagram and a process flow chart of a palladium half-tube hydrogen sensor of the present invention;
[0023] Figure 2 This is a process flow chart for preparing the nanowire substrate of the present invention;
[0024] Figure 3 This is a SEM image of the front and back palladium half-tubes transferred onto a silicon substrate of the present invention;
[0025] Figure 4 This is a SEM image of a palladium half-tube supported by nanowires of the present invention;
[0026] Figure 5 The figure is the resistance response diagram of the sensor of the present invention to 1% and 0.1% hydrogen at room temperature. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments 1-3 of the present invention and the attached Figures 1 to 5 , the technical solution of the present invention is clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] The present invention provides a method for preparing a suspended palladium nano-half-tube material based on metal contact, comprising the following steps:
[0029] S1: firstly, polyvinyl alcohol is mixed with deionized water, and stirred evenly by a magnetic stirrer, and a precursor solution is obtained after degassing, and the precursor solution is electrospun and received by a rectangular hollow template to obtain uniform polyvinyl alcohol nanofibers with an oriented structure;
[0030] S2: Evaporate metal palladium on the polyvinyl alcohol nanofibers obtained in S1, and simultaneously evaporate tin oxide on the substrate, and transfer the fibers to the substrate by water vapor dissolution to obtain a suspended palladium nano-half-tube material. Since electron beam evaporation has directionality, a half-tube structure can be formed on the surface of the nanofibers to obtain a suspended palladium nano-half-tube material based on metal contact.
[0031] Example 1
[0032] S1: Mix 1 g of 1788 polyvinyl alcohol with 10 mL of deionized water and stir evenly with a magnetic stirrer at a temperature of 65 °C, a stirring time of 12 h, and a stirring rate of 600 r·min. -1 , degassing rate is 3000r·min -1 The degassing time is 3 min. The precursor solution is electrospun. During the spinning process, the pushing speed is 0.1 mm·min -1 , the DC voltage is 16kV, the distance between the needle tip and the receiving template is 15cm, the spinning time is 5min; the temperature is 40℃, the humidity is 20RH; a rectangular hollow template is used for receiving, and the size of the hollow part of the rectangular hollow template is 100mm*20mm; uniform polyvinyl alcohol nanofibers with oriented structure are obtained;
[0033] S2: Evaporate 10nm of metal palladium onto the polyvinyl alcohol nanofibers obtained in S1. Before evaporation, reduce the vacuum degree of the cavity to 5*10 -4 Below, the coating rate is 0.8nm / min, and 10nm tin oxide is evaporated on the nanowire substrate at the same time. Before evaporation, the vacuum degree of the chamber is reduced to 5*10 -4 Below, the coating rate is 0.5nm / min, and a nanowire substrate with a tin oxide film is obtained, and then the fiber is transferred to the substrate by water vapor dissolution method; due to the directionality of electron beam evaporation, a semi-tube structure can be formed on the surface of the nanofiber to obtain a suspended palladium nano-semi-tube material based on metal contact.
[0034] Combination Figure 1In the present invention, nanofibers are placed on different transfer substrates through polyvinyl alcohol, and the sample is placed in a closed space, a burner filled with 50 to 80 ml of deionized water is placed in the space, heated to 80 to 90°C, and left to stand for 24 hours. This step uses water vapor to dissolve polyvinyl alcohol. Since the semi-tube film is only 5 to 15 nm and has a fragile structure, this method can improve the transfer efficiency and yield rate compared to dripping and spraying water mist. After dissolution, the nanofibers are removed to form a palladium metal film with a semi-tube structure. The method of this step can transfer the semi-tube to any substrate. Specifically, we have achieved transfer on PET, gold film, PI, silicon wafer, ceramic, fabric and nanowire substrates, which fully proves the versatility of the method.
[0035] Combination Figure 2 The present invention uses nanowires with line width / groove width = 200 / 400 or 200 / 600 as a substrate, and the substrate is obtained by nanoimprinting. Specifically, a tackifier, isopropyl alcohol and an organic UV-curable polymer are sequentially spin-coated on a 2-inch silicon wafer and heated to solidify. Then, the PET nanowire template is imprinted onto the silicon wafer by UV imprinting to achieve the suspension of the nano half-tube.
[0036] from Figure 3 In the figure, we can see the palladium half-tube structure prepared using the PVA sacrificial template. Figure 3 (a) and Figure 3 (b) shows the front and back of the half-tube structure. The diameter of the half-tube is about 200-300nm and the wall thickness is 10nm. From the front structure, it can be clearly seen that the cross-section of the palladium half-tube structure is a semicircle, and the back structure can also see the complete and clear groove shape, which proves that this method can prepare the palladium half-tube structure. At the same time, the 10nm wall thickness is very thin and the half-tube is relatively fragile, but the water vapor transfer method can achieve large-area structure preparation.
[0037] from Figure 4 (a) As can be seen in the figure, the palladium half-tube transferred to the nanowire substrate realizes a suspended structure, similar to a "bridge" shape. Figure 4 (b) In the figure, we can see that the half-tube structure is suspended due to the support of the nanowires. The cantilever beam structure beyond the nanowires will collapse, that is, Figure 4 (b) Enlarged view.
[0038] from Figure 5It can be seen that the gas-sensitive test graph is a resistance response test of the material to 1% and 0.1% hydrogen. It can be seen that the material still maintains a stable resistance change after dozens of cycles, with a large response value of about 12%, and a response time of less than 100s. When the hydrogen concentration is above 4%, there is an explosion risk. In the performance goals of the U.S. Department of Energy's fixed and automotive hydrogen safety sensors, the concentration detection capability must be less than 4%, and the detection limit must reach 0.1%. Our material performance can meet the target requirements, and the material preparation is simple, with research and application prospects.
[0039] The suspended palladium nanometer half-tube material obtained by the present invention can be evaporated with 10nm tin oxide (SnO2) material on the nanowire substrate. Electron exchange and barrier change will occur at the contact interface between palladium and tin dioxide, and a Schottky junction will be formed, which is helpful to improve the gas sensing performance. In the experiment, tin oxide was evaporated on the substrate. Because the substrate is a nanowire, only the tin oxide on the line can contact the palladium half-tube, which will form a structure similar to a parallel circuit. The palladium half-tube is compared to a wire, and the tin oxide nanowire part is compared to a resistor. Here, the tin oxide is also 10nm tin oxide evaporated by electron beam. The complexity of the structure and the contact interface of different materials are enhanced. There will be electron movement caused by the difference in barrier energy levels at the contact interface, that is, a heterogeneous structure, which is helpful to improve the gas sensing performance.
[0040] The present invention adopts the water vapor dissolution method to transfer the palladium half-tube fiber network with an oriented structure to the nanowire substrate. The two structures are in a cross shape, and conductive silver paste is applied to both ends of the sample (suspended palladium half-tube structure) to form electrodes, which can be made into a hydrogen sensor.
[0041] As for the microstructure, the microstructure of the suspended palladium nano-half-tube material is mainly a palladium half-tube structure film with a thickness of about 10nm placed on a nanowire substrate with a width of 200nm and a gap of 400nm. In the present invention, tin dioxide is evaporated on the substrate. This material has an electronic modulation effect when in contact with the palladium half-tube, which is also helpful for enhancing the gas sensing performance. The half-tube structure is Figure 1 and Figure 3 As can be seen in the figure, the cross section is a semicircular shape with a diameter between 200-300. This semicircular structure and a 10nm thick membrane give the structure a very high specific surface area. At the same time, unlike the planar structure, the suspended part of the semi-tube structure is added to the nanowire substrate, which increases the specific surface area and reduces the restriction of the substrate on the semi-tube structure. During the gas test, palladium will absorb hydrogen and expand. Reducing the restriction of the substrate can also improve the gas sensing performance.
[0042] Example 2
[0043] S1: Mix 2 g of 1788 polyvinyl alcohol with 10 mL of deionized water, and stir them evenly with a magnetic stirrer. The temperature of the magnetic stirrer is 85 °C, the stirring time is 12 h, and the stirring rate is 600 r·min. -1 , degassing rate is 3000r·min -1 The degassing time is 5 min. The precursor solution is electrospun. During the spinning process, the pushing speed is 0.2 mm·min -1 , the DC voltage is 20kV, the distance between the needle tip and the receiving template is 20cm, the spinning time is 15min; the temperature is 40℃, the humidity is 30RH; a rectangular hollow template is used for receiving, and the size of the hollow part of the rectangular hollow template is 100mm*20mm; uniform polyvinyl alcohol nanofibers with oriented structure are obtained;
[0044] S2: Evaporate 10nm of metal palladium onto the polyvinyl alcohol nanofibers obtained in S1. Before evaporation, reduce the vacuum degree of the cavity to 5*10 -4 Below, the coating rate is 0.8nm / min, and 10nm tin oxide is evaporated on the nanowire substrate at the same time. Before evaporation, the vacuum degree of the chamber is reduced to 5*10 -4 Below, the coating rate is 0.5nm / min, and a nanowire substrate with a tin oxide film is obtained, and then the fiber is transferred to the substrate by water vapor dissolution method; due to the directionality of electron beam evaporation, a semi-tube structure can be formed on the surface of the nanofiber to obtain a suspended palladium nano-semi-tube material based on metal contact.
[0045] Example 3
[0046] S1: 1.5 g of 1788 polyvinyl alcohol was mixed with 10 mL of deionized water, and stirred evenly with a magnetic stirrer at a temperature of 70 °C, a stirring time of 12 h, and a stirring rate of 600 r·min. -1 , degassing rate is 3000r·min -1 The degassing time is 5 min. The precursor solution is electrospun. During the spinning process, the pushing speed is 0.15 mm·min -1 , the DC voltage is 18kV, the distance between the needle tip and the receiving template is 17cm, the spinning time is 10min; the temperature is 40℃, the humidity is 25RH; a rectangular hollow template is used for receiving, and the size of the hollow part of the rectangular hollow template is 100mm*20mm; uniform polyvinyl alcohol nanofibers with oriented structure are obtained;
[0047] S2: Evaporate 10nm of metal palladium onto the polyvinyl alcohol nanofibers obtained in S1. Before evaporation, reduce the vacuum degree of the cavity to 5*10 -4Below, the coating rate is 0.8nm / min, and 10nm tin oxide is evaporated on the nanowire substrate at the same time. Before evaporation, the vacuum degree of the chamber is reduced to 5*10 -4 Below, the coating rate is 0.5nm / min, and a nanowire substrate with a tin oxide film is obtained, and then the fiber is transferred to the substrate by water vapor dissolution method; due to the directionality of electron beam evaporation, a semi-tube structure can be formed on the surface of the nanofiber to obtain a suspended palladium nano-semi-tube material based on metal contact.
[0048] The present invention provides a suspended palladium nanometer half-tube material based on metal contact, and the unique structural design of the suspended palladium nanometer half-tube significantly increases the specific surface area. By utilizing the half-tube and the suspension structure, the contact area with the gas molecules can be effectively increased, thereby enhancing the reaction rate and further improving the performance of the sensor. By reducing the inhibitory effect of the base material on the palladium film, the present invention can increase the expansion response speed of the palladium film during the hydrogen reaction process. This improvement enables the sensor to respond quickly to changes in a dynamic environment, and is suitable for real-time monitoring and control.
[0049] The present invention provides a preparation method of a suspended palladium nano-half-tube material based on metal contact, wherein the preparation method uses metal oxide as a base material in contact with the palladium half-tube, and can effectively change the chemical reactivity and conductivity of the sensor by adjusting the interface characteristics of the metal and the metal oxide. This design not only improves the sensitivity of the gas sensor, but also improves the response speed, especially in the detection of low-concentration gases. The water vapor transfer method is combined with PVA nanofibers as a sacrificial template to achieve low-cost and high-efficiency preparation of a 10nm-level thin film groove structure. This method not only reduces the production steps, but also reduces material consumption, and has good industrialization prospects. Through the contact between the metal and the metal oxide, the energy level arrangement characteristics of the material can be adjusted, and the transmission characteristics of the charge carriers at the interface can be optimized. This change helps to improve the efficiency of electronic devices and provides new ideas for subsequent integrated circuit and sensor designs.
[0050] The present invention provides an application of a suspended palladium nano-half-tube material based on metal contact, which can be transferred to a variety of substrates, so that it has a wide range of application potentials in the fields of sensors, catalysts, etc., especially in the fields of gas detection, environmental monitoring and safety protection.
Claims
1. A method for preparing a suspended palladium nanotube material based on metal contact, characterized in that: The following steps are involved: S1: mixing polyvinyl alcohol and a solvent in a mass ratio of 1 to 2:10, stirring evenly by magnetic stirring, degassing to obtain a precursor solution, electrospinning the precursor solution, receiving it with a template, and obtaining polyvinyl alcohol nanofibers; S2: Vapor-deposit metal palladium on the polyvinyl alcohol nanofibers obtained in S1, and simultaneously vapor-deposit tin oxide on the substrate, and transfer the fibers to the substrate by water vapor dissolution method to obtain a suspended palladium nano-half-tube material.
2. The method for preparing a suspended palladium nano-half-tube material based on metal contact according to claim 1, characterized in that: The temperature of magnetic stirring in S1 was 65-85℃, the stirring time was 12h, and the stirring rate was 600r·min -1 , degassing rate is 3000r·min -1 The degassing time is 3 to 5 minutes.
3. The method for preparing a suspended palladium nano-half-tube material based on metal contact according to claim 1, characterized in that: The pushing speed during the spinning process in S1 is 0.1-0.2 mm·min -1 , the DC voltage is 16-20 kV, the distance between the needle tip and the receiving template is 15-20 cm, and the spinning time is 5-15 min.
4. The method for preparing a suspended palladium nano-half-tube material based on metal contact according to claim 1, characterized in that: The temperature of the spinning process in S1 is 40°C and the humidity is 20-30RH; the template is a rectangular hollow template with a hollow size of 100mm*20mm.
5. The method for preparing a suspended palladium nano-half-tube material based on metal contact according to claim 1, characterized in that: The metal palladium in S2 is 10nm, the tin oxide is 10nm, and the coating rate is 0.8nm / min.
6. The method for preparing a suspended palladium nano-half-tube material based on metal contact according to claim 1, characterized in that: The substrate described in S2 is any one of PET, gold film, PI, silicon wafer, ceramic, fabric and nanowire.
7. A metal contact-based suspended palladium nano-half-tube material obtained by the preparation method according to any one of claims 1 to 6, characterized in that: The suspended palladium nanometer half-tube material is a half-tube structure.
8. The use of a metal-contact-based suspended palladium nano-half-tube material according to claim 7, characterized in that: The suspended palladium nano-half-tube material is used in preparing a hydrogen sensor.
Citation Information
Patent Citations
Palladium-doped stannic oxide wrapped carbon nano tube as well as preparation method and application of nano tube
CN103713016A
Resistance-type humidity sensor based on Pd / SnO2 / Si heterojunction and preparation method thereof
CN105223238A
Preparation method of plasma-treated nano-fiber hydrogen sensing material
CN111349974A
Micro-pattern structure transfer printing method and micro-pattern structure substrate
CN112606583A
Rapidly disposable memory with water-soluble substrate and manufacturing method thereof
KR1020170008457A